Silage Making in Polythene Bags - Shanti, M.; Shashikala, T.; Susheela, R.; Anuradha, M. (Chronicle of Bioresource Management, 2023)
India is the world’s leading producer of milk. The increase was more than 12 times since independence. However, productivity is a matter of concern. The production technologies of feed and fodder need to be more versatile for sustainable milk and meat production. Nevertheless, seasonal variations in supply and demand of fodder often affect the milk production which needs to be addressed. Use of preserved feed like silage is extremely limited in India compared to rest of the world. Often the cost of infrastructure associated with forage preservation is intimidating the farming community, besides, the knowhow on ensiling. This article discusses the aspects on suitability of crops, methodologies and advances in silage making.